The Use of Games for Learning in Primary Schools: A Bibliometrics Analysis of The Scopus Database - Afib Rulyansah; Emy Yunita Rahma Pratiwi; Ribut Prastiwi Sriwijayanti; Ani Anjarwati (Jurnal Basicedu, 2022)
Elementary school learning that is integrated with games can increase student motivation in learning so that it can have a positive impact on learning outcomes. The bibliometric review used in this research aims to analyze articles that discuss the use of games at the elementary school level published in the Scopus database indexed journal for the period 2013-2022. A total of 122 articles discussing the integration of games in primary school level learning were analyzed. The review findings show that there was a significant increase in the number of publications in 2016-2021, around 77.87% of articles were published in that period. Spain and Indonesia dominate the number of publications. Four authors with 3 publications each are influential authors. Data visualization shows that this research topic can be grouped based on the type of game, type of game, subject of study, learning approach, type of learning, subject involved in research, and a number of topics that have the potential to be integrated with other topics to obtain novelty. The findings of this study can help relevant researchers to recognize research trends in the use of games for primary school learning globally and recommend directions for further research.